Development of Comic-Based Physics Modules to Improve Students' Critical Thinking Ability on Vibration and Wave Materials - Yuliana Nensi Putri; Nurul Ain; Kurriawan Budi Pranata (Department of Physics Education, Universitas Mataram, 2022)
This development research will produce a product in the form of a comic-based physics module on vibration and wave material. The research objectives are to determine: (1) Feasibility, (2) practicality, and (3) the effectiveness of the module to improve students' critical thinking skills. The research uses Research & Development which refers to the development of ADDIE namely Analysis, Design, Development, Implementation and Evaluation. The analysis and design stages are developed based on the needs of students by displaying the discussion of comic characters which aims to make students able to think critically. The product validation stage involves 4 validators, namely two media experts and 2 material experts to assess the module design, material feasibility, and language feasibility. The results of the validation of the feasibility of the module obtained 82% from the 2 media experts and 82% from the 2 material experts–all of which were within the category of